PENGOLAHAN LIMBAH CAIR RUMAH MAKAN MENGGUNAKAN METODE MULTI SOIL LAYERING (MSL) - Fathiya Nabila; Nur Aida; Aulia Rohendi (Program Studi Teknik Lingkungan Fakultas Sains dan Teknologi UIN Ar-Raniry Banda Aceh, 2022)
Waste is waste that comes from the process of making or using an industrial or domestic product. The waste generated is in the form of liquid and solid. Waste is also an unused waste material that has a negative impact on society if it is not managed properly. Liquid waste or waste is water that cannot be used anymore and can have a negative impact on humans and the environment. Multi Soil Layering (MSL) system is a liquid waste treatment method that utilizes the ability of the soil as the main medium in removing pollutants in liquid waste. The purpose of this study was to determine how to treat restaurant liquid waste using the Multi Soil Layering (MSL) method for the parameters of pH, BOD, COD, and TSS. Based on research, the Multi Soil Layering (MSL) reactor is effective in improving pH values ​​and reducing COD and TSS so that restaurant wastewater does not pollute the environment and can prevent negative impacts caused by restaurant liquid waste.